A warm-up strategy with or without voluntary contraction on athletic performance, lower-leg temperature, and blood lactate concentration. - Seunghee Lee; Junhyeong Lim; Jihong Park (PLoS ONE, 2024)
It is unclear whether temperature-related warm-up effects can be accomplished by passive warm-up (e.g., by external heat). Therefore, this study compared the effects of two different warm-up protocols with and without voluntary contraction on subsequent sprinting and jumping performance. Eighteen healthy male collegiate students (23.3 ± 2.4 years, 173.8 ± 7.2 cm, 70.5 ± 9.3 kg) randomly experienced 10 min of active (jogging on a treadmill; belt speed: 9.0 km/h at a 1% incline) and passive warm-up (lying down in the warm-up chamber; inner ambient temperature set at 35°C) protocols, followed by ten sets of intermittent exercises in two separate sessions. Athletic performance, lower-leg muscle temperature, and blood lactate concentration were statistically compared using analysis of variance with Tukey-Kramer post-hoc comparisons. Cohen's d effect sizes (ES) were also calculated. There was no warm-up protocol effect over time on 20 m sprint times (condition × time: F9,323 = 1.26, p = 0.25). Maximal vertical jump heights were different (condition × time: F9,323 = 2.0, p = 0.04) such that subjects who performed the active warm-up protocol jumped higher (51.4 cm) than those who did the passive warm-up (49.2 cm, p = 0.04). There was a warm-up protocol effect over time on lower-leg muscle temperature (condition × time: F12,425 = 13.99, p<0.0001) in that there was a 5.5% and 5.8% increase after active (32.8 to 34.6°C, ES = 2.91) and passive (32.9 to 34.9°C, ES = 3.28) warm-up protocols, respectively. Blood lactate concentration was different (condition × time: F2,85 = 3.61, p = 0.03) since the values at the post-warm-up measurements were different between warm-up conditions (active: 4.1 mmol/L; passive: 1.5 mmol/L, p = 0.004, ES = 1.69). Subsequent sprint and jump performance did not differ between the duration- and muscle temperature-matched active and passive warm-up protocols. Non-thermal effects from the warm-up activity may be minimal for sprinting and jumping performance in recreationally active males.